2011
DOI: 10.5194/acp-11-7875-2011
|View full text |Cite
|
Sign up to set email alerts
|

Forest-atmosphere exchange of ozone: sensitivity to very reactive biogenic VOC emissions and implications for in-canopy photochemistry

Abstract: Abstract. Understanding the fate of ozone within and above forested environments is vital to assessing the anthropogenic impact on ecosystems and air quality at the urbanrural interface. Observed forest-atmosphere exchange of ozone is often much faster than explicable by stomatal uptake alone, suggesting the presence of additional ozone sinks within the canopy. Using the Chemistry of AtmosphereForest Exchange (CAFE) model in conjunction with summer noontime observations from the 2007 Biosphere Effects on Aeros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 75 publications
(91 reference statements)
4
81
2
Order By: Relevance
“…Since the OH reactivity is highly underestimated due to missing sinks, it is also possible that our modelled O 3 and NO 3 reactivities are underestimated due to potentially missing sinks (Wolfe et al, 2011, and references therein).…”
Section: O 3 Reactivitymentioning
confidence: 99%
“…Since the OH reactivity is highly underestimated due to missing sinks, it is also possible that our modelled O 3 and NO 3 reactivities are underestimated due to potentially missing sinks (Wolfe et al, 2011, and references therein).…”
Section: O 3 Reactivitymentioning
confidence: 99%
“…Improvements can be expected by more accurate representations of land cover (and subsequent changes) (Hardacre et al, 2015), or by including a more process-based model of deposition that depends on soil moisture and vapor deficit (Büker et al, 2012;Pleim et al, 2001). There is also evidence that a significant fraction of the O 3 uptake observed over forest canopies is actually an unaccounted for chemical sink (Kurpius and Goldstein, 2003;Rannik et al, 2012;Schade and Goldstein, 2003;Wolfe et al, 2011), but changes in this above-canopy chemistry are not captured in our current set of simulations.…”
Section: J a Geddes Et Al: Land Cover Change Impacts On Atmospherimentioning
confidence: 81%
“…The impacts of canopy uptake and canopy chemistry resulting from changes in vegetation density and composition could be explored in more detail with future work using a 1-D forest canopy-chemistry model (e.g., Wolfe, 2011;Ashworth et al, 2015) for the regions where we project large impacts. We have assumed that the basal emissions from the soil after the disturbance will be the same as those prior to the disturbance, but large-scale tree mortality and forest succession have the potential to alter soil biogeochemistry (Gao et al, 2015;Norton et al, 2015;Trahan et al, 2015).…”
Section: J a Geddes Et Al: Land Cover Change Impacts On Atmospherimentioning
confidence: 99%
“…This indicates that SQTs and escpecially β-caryophyllene ( Figure S8d) have much higher effect for example on local ozone deposition than MTs. Several studies have shown that measured ozone deposition fluxes cannot be 25 explained by modelled stomatal and known non-stomatal sinks, such as reactions with measured VOCs in the gas phase (Clifton et al 2017;Wolfe et al 2011;Rannik et al 2012). Higher than expected impact of the SQTs could explain at least part of the discrepancy.…”
Section: Reactivity Of Measured Bvocsmentioning
confidence: 99%